SINTESIS KARBOKSIMETIL KITOSAN DAN APLIKASINYA SEBAGAI ADSORBEN Pb(II) - , DEWI KURNIATI S.Si ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The synthesis of carboxymethyl chitosan and its application as adsorbent of Pb(II) has been studied. Synthesis of carboxymethyl chitosan was performed by reacting chitosan and chloroacetic acid at 78 Â°C for 12 hours. The âCOOH content of carboxymethyl chitosan was determined using potentiometric titration method. The product of carboxymethyl chitosan was characterized by infrared spectrophotometry and Gas Sorption Analyzer (GSA). Adsorption process of Pb(II) was conducted in batch system and measured as a function of pH, contact time, and initial concentration of Pb(II). The adsorption of Pb(II) was examined using initial concentration of 100 mg/L and pH was varied from 2-7. Total ion Pb(II) adsorbed was determined by calculating the difference of metal ion concentration in the medium before and after adsorption using atomic absorption spectrometry method. FT-IR spectra showed that carboxymethyl chitosan exhibited a new C=O absorption peak of âCOOH group at 1743 cm -1 . Surface areas of chitosan and carboxymethyl chitosan measured by N2 adsorption were 0.524 and 1.125 m 2 /g, the total pore volume of chitosan and carboxymethyl chitosan were 2.073 x10 -3 and 2.579 x10 -3 cm 3 /g, respectively. The content of âCOOH in the synthesized carboxymethyl chitosan was 51.53 cmol/kg. The optimum pH in the adsorption of Pb(II) on chitosan and on carboxymethyl chitosan was observed at 4. Adsorption kinetic for both adsorbents was observed to follow pseudo second order with rate constants of 0.146 g mmol min -1 and 0.114 g mmol min -1 , respectively. Adsorption capacities of Pb(II) on chitosan and carboxymethyl chitosan were 0.125 and 0.289 mmol/g, respectively. Apparently the coexistence of Ni(II) affected the Pb(II) adsorption capacity on chitosan and carboxymethyl chitosan adsorbents, and the strongest effect was observed in concentration ratio of Pb(II):Ni(II) of 1:1 (mol/mol) and 2:1(mol/mol), respectively.